Hawaiian Plants with Beneficial Effects on Sleep, Anxiety, and Mood, etc. - Pornphimon Meesakul; Tyler Shea; Shi Xuan Wong; Yutaka Kuroki; Shugeng Cao (MDPI AG, 2023)
Diverse chemical messengers are responsible for maintaining homeostasis in the human body, for example, hormones and neurotransmitters. Various Hawaiian plant species produce compounds that exert effects on these messengers and the systems of which they are a part. The main purpose of this review article is to evaluate the potential effects of Hawaiian plants on reducing pain and anxiety and improving sleep and mood. A comprehensive literature search was conducted in SciFinder, PubMed, Science Direct, Scopus, Google Scholar, and Scientific Information Database between 2019 and 2023 to identify related articles. Results indicate that several Hawaiian plant species, such as M. citrifolia and P. methysticum, have medicinal properties associated with these effects. These plants have been used in traditional Hawaiian cultural practices for centuries, suggesting their potential to benefit human health and well-being. This review presents a comprehensive analysis of the available evidence concerning the potential impacts of Hawaiian plants on sleep, anxiety, mood, and pain.